A System Dynamics Approach to Understanding the deep Magma Plumbing System Beneath Dominica (Lesser Antilles) - Solaro, Clara; Balcone-Boissard, Hélène; Morgan, Daniel Joseph; Boudon, Georges; Martel, Caroline; Ostorero, Léa (Frontiers in Earth Science, 2020)
The dynamic of magmatic systems seeks to model the time dependent behavior of storage and ascent processes. We do this through a combination of the Crystal System Approach and Fe-Mg interdiffusion in orthopyroxene. This offers an opportunity to trace the pre-eruptive dynamics of magma plumbing systems, both in space and time. We demonstrate this novel approach on two large silicic eruption (about 3-5 km3 DRE/eruption) that occurred in the central part of Dominica Island (Lesser Antilles arc): the eruptions of Layou (~51 ka) from Morne Diablotins, and Roseau (~33 ka) from Morne Trois Pitons-Micotrin. For the Roseau eruption, two magmatic environments are identified on the basis of orthopyroxene composition, with a dominant reverse-zoning pattern from 50-54 to 54-59 mol% enstatite (En), indicating interaction with hotter magma. For the Layou eruption, three magmatic environments are observed: En47-51, En51-53 and En53-58. The normal-zoning pathway from En51-53 to En47-51 is significantly registered by crystals, interpreted as convective mixing in a zoned reservoir. The reverse-zoning pathway from En47-51 to En51-53 and also En53-58 is also significantly present, supporting the mixing within the zoned reservoir but also suggesting a mixing with a hotter magma, possibly stored in another part of the mush. The crystal and glass compositions (melt inclusion and matrix glass) from both studied eruptions suggest heating and mixing between different magma pocket in the mush that were the dominant process for mobilising eruptible magma. In parallel, we constrain the associated pre-eruptive timescales by modelling the diffusive relaxation of Fe-Mg chemical gradients that originated with the zonation of the same orthopyroxene crystals. Diffusion modelling was considered along the b-axis of 66 zoned orthopyroxene crystals for these two eruptions, at a magmatic temperature of 850±25°C. In the light of these results, we propose that the Layou and the Roseau magma reservoirs were rejuvenated and heated by ~25 to 50 °C about 10 years prior to eruption by the injection of an underplating, hotter magma, creating the observed dominant reverse-zoning patterns of the erupted orthopyroxenes. We thus have evidence that silicic mush can be re-mobilized over timescales of decades prior to eruption.